Enhancement of Thermoelectric Performance in Oligomeric PEDOT‐SWCNT Nanocomposite via Band Gap Tuning. Issue 31 (20th August 2018) - Maity, Shilpa; Sepay, Nayim; Kulsi, Chiranjit; Kool, Arpan; Das, Sukhen; Banerjee, Dipali; Chatterjee, Krishanu
Abstract: Organic thermoelectric (TE) materials, inspite of their low cost, non‐toxicity, easy availability, show a low thermoelectric figure of merit (ZT). Herein we report ZT > 0.04 for tosylate doped poly(3, 4 ethylenedioxythiophene) (PEDOT‐Tos) with single walled carbon nanotubes (SWCNT) which is higher than the reported values for bulk nanostructured polymer based composites. The underlying reason for the enhancement of the transport properties is the morphological transformation of the nanocomposites exhibiting an increase degree of ordered structure of the samples with the increase of SWCNT content as is observed from XRD, UVVIS and FESEM studies. This increase in the ordered structure is due to the decrease in band gap that was found in DFT calculations which in turn increases the electrical conductivity which is responsible for the enhanced power factor. Further the SWCNTs introduce the interfaces that reduce the thermal conductivity due to scattering of phonons which further contributes to the enhancement in the figure of merit. Abstract : Band gap tuning by incorporation of in SWCNT in PEDOT‐Tos increases the degree of crystallinity which decreases the thermoelectric power (S) and in turn increases the carrier concentration pushing the Fermi level (EF ) into the conduction band increasing the electrical conductivity (σ). As a result there is an overall increase in thermoelectric power factor which help in the increment of ZT.